COVID-19 pandemic and perceived stress in Information Technology professionals - Saira Bano; Nimty Raina Ambardar; Anuradha Rajiv Joshi (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Novel coronavirus disease (COVID-19), a pandemic was declared by WHO on 11 March 2020. The lockdown had an evident impact on various sectors including the Information Technology sector. Few studies have been conducted to find out the levels of stress in Information Technology professionals. During the COVID-19 pandemic, all employees of Information Technology companies were informed to work remotely at their homes without any prior information, training and mental acceptance i.e. 'work from home'. Information technology professionals have occupational stress &working from home during COVID-19 has added mental stress. The present study was planned to assess the impact of the COVID-19 pandemic on perceived stress in Information Technology professionals. Methods: The present study was a cross-sectional observational study. Volunteers of the Information Technology sector (n=200) of either sex in the age group of 25 to 55 years participated in the study. PSS was administered through Google Forms and scores were analyzed. Results: The association of various stressors with PSS was done which showed a significantly positive association. The mean PSS score of subjects was 23.53 ± 7.39. Twelve (6%) employees had mild, twenty (60%) had moderate and sixty-eight (34%) had high stress levels. This study explored that IT professionals experienced an additional level of stress during the COVID-19 pandemic. Conclusion: The present study concluded statistically significant moderate levels of stress in IT professionals of either sex with the outbreak of the COVID-19 pandemic.